Qatar : Selected Issues. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2018)
This Selected Issues paper analyzes the performance and vulnerabilities of Qatar's nonfinancial corporate (NFC) sector. Qatar's NFC sector is sizable in terms of the overall share of economic activity. The total turnover of these companies was USD 28 billion in 2016. Assets of listed and non-listed NFCs in Qatar were estimated at about 115 percent of non-hydrocarbon GDP in 2016. Although profitability of Qatari corporates, as measured by Return on Equity and Return on Assets, has declined, it is still high. Qatari companies remain resilient in the face of moderate to severe interest and earnings shocks, as median Interest Coverage Ratio of Qatari firms remains well above 1. The impact of these shocks on debt-at-risk and firms-at-risk is also limited.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet